Penerapan Model Pembelajaran TTW Untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN 151 Bunne - Abdul Halik; Muhammad Asrul Sultan; Nurul Asmarida (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The problem this research is the low writing learning outcomes of class V students. This research aims to determine the application of the TTW learning model to determine the increase in paragraph writing learning outcomes in class V at SDN 151 Bunne. The approach used in this research is a qualitative approach with a type of classroom action research to improve the quality of the learning process in the classroom. The learning results the first cycle of teacher and student are in the sufficient category (C) while student learning are in the poor category (K). The learning results cycle II of teacher and student are the sufficient category (C) while student learning are in the sufficient category (C). The learning results cycle III of teacher and student are the good category (B) while student learning are in the sufficient category (C). The learning results cycle IV of teacher and student are in the good category (B) while the student learning are in the sufficient category (B). The conclusion of the research is that by implementing the TTW type cooperative learning model, it can improve the paragraph writing learning outcomes of Class V Students at SDN 151 Bunne, Soppeng Regency.